2016
DOI: 10.1103/physrevc.93.024905
|View full text |Cite
|
Sign up to set email alerts
|

Centrality dependence of pion freeze-out radii in Pb-Pb collisions atsNN=2.76 TeV

Abstract: We report on the measurement of freeze-out radii for pairs of identical-charge pions measured in Pb-Pb collisions at √ s NN = 2.76 TeV as a function of collision centrality and the average transverse momentum of the pair k T . Three-dimensional sizes of the system (femtoscopic radii), as well as direction-averaged onedimensional radii are extracted. The radii decrease with k T , following a power-law behavior. This is qualitatively consistent with expectations from a collectively expanding system, produced in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 60 publications
5
36
0
Order By: Relevance
“…The average radii obtained in this analysis are consistent with the results reported in Ref. [31]. As expected, the radii are larger in more central collisions and at smaller k T values, the latter reflecting the effect of radial flow [7,32].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The average radii obtained in this analysis are consistent with the results reported in Ref. [31]. As expected, the radii are larger in more central collisions and at smaller k T values, the latter reflecting the effect of radial flow [7,32].…”
supporting
confidence: 81%
“…Other than being differential in the event plane, this analysis is similar in most aspects to the analysis reported in [31], and further details can be found there. The results reported below were obtained with the second harmonic event plane [27] determined with the TPC tracks.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…This effect appears to be stronger at LHC energies than at RHIC energies [35,36]. It was studied by the ALICE collaboration for pions in Pb-Pb collisions at 2.76 TeV [19] at different centralities. This work extends this study to kaons and compares the obtained transverse radii with those found in the analysis for pions and to the model calculations discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…ALICE has excellent capabilities to study femtoscopy observables due to good track-by-track particle identification (PID), particle acceptance down to low transverse momenta p T , and good resolution of secondary vertices. We already studied pion correlation radii in Pb-Pb collisions at 2.76 TeV [9,19]. Pion femtoscopy showed genuine effects originating from collective flow in heavy-ion collisions, manifesting as a decrease of the source radii with increasing pair transverse mass m T = (k 2 T + m 2 ) 1/2 [14,20], where k T = |p T,1 + p T,2 |/2 is the average transverse momentum of the corresponding pair and m is the particles mass.…”
Section: Introductionmentioning
confidence: 99%